2022
DOI: 10.1021/acs.molpharmaceut.2c00838
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Dynamics in Intrinsic Physicochemical Profiles of Market-Stage Antibody-Based Biotherapeutics

Abstract: Adequate stability, manufacturability, and safety are crucial to bringing an antibody-based biotherapeutic to the market. Following the concept of holistic in silico developability, we introduce a physicochemical description of 91 market-stage antibody-based biotherapeutics based on orthogonal molecular properties of variable regions (Fvs) embedded in different simulation environments, mimicking conditions experienced by antibodies during manufacturing, formulation, and in vivo. In this work, the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…MD is important for a fuller understanding of antibody systems as it provides insight into the flexibility and fluctuations of antibody structure and developability parameters ( 29 , 33 , 34 , 117 , 119 , 120 ). Specifically, Park and Izadi found that antibody developability surface descriptor parameters (e.g., positive electrostatic potential on the surface of the CDR region ( 121 )) vary extensively as a function of the structure prediction method used, which is in line with the findings in this manuscript (Supplementary File).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MD is important for a fuller understanding of antibody systems as it provides insight into the flexibility and fluctuations of antibody structure and developability parameters ( 29 , 33 , 34 , 117 , 119 , 120 ). Specifically, Park and Izadi found that antibody developability surface descriptor parameters (e.g., positive electrostatic potential on the surface of the CDR region ( 121 )) vary extensively as a function of the structure prediction method used, which is in line with the findings in this manuscript (Supplementary File).…”
Section: Discussionmentioning
confidence: 99%
“…However, mAbs are usually exposed to a wider range of solution pH (4.8-9) during production and formulation (10,97). Also, antibody variable region charge in acidic pH has proven to be a critical factor in IgG mAb pharmacokinetics (98)(99)(100) and product formulation (29). Therefore, we included the sequence-based variable region charge measures in 14 pH points (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in our analysis.…”
Section: Developability Parameter Redundancy May Be Reduced Through A...mentioning
confidence: 99%
See 2 more Smart Citations
“…This option requires the ability to discriminate candidates that have liabilities. Many experimental [22][23][24][25][26][27][28] and computational [29][30][31][32][33][34][35][36][37][38][39] methods of candidate assessment are available and have been previously discussed at length [40][41][42][43] . The second option is to generate drug candidates de-risked for developability by design.…”
Section: Introductionmentioning
confidence: 99%